Can someone SMART redo these questions I mean I made a seven and I did all I could I need to know what went wrong
1 answer:
2. 8x -28 = -140 8x -28 + 28 = -140 + 28 8x = -112 8x/8 = -112/8 x = -14 3. -9 + x/3 = -23 -9 + 9 + x/3 = -23 + 9 x/3 = -14 x/3/3 = -14/3 x = -14/3 4. x/-1.5 - 3.5 = -13.5 x/-1.5 - 3.5 + 3.5 = -13.5 + 3.5 x/1.5 = -10 x/-1.5/-1.5= -10/-1.5 x = 20/3 5.-6(x + 3) = -36 -6x - 18 = -36 -6x - 18 + 18 = -36 + 18 -6x = -18 -6x/-6 = -18/-6 x = 3 6. k + 3.7/9.8 = -0.22 k + 3.7/9.8/9.8 = -0.22/9.8 k + 3.7 = -2.156 k + 3.7 - 3.7 = -2.156 - 3.7 k = -5.856 7. 12(x - 6) = -108 12x - 72 = -108 12x - 72 + 72 = -108 + 72 12x = -36 12x/12 = -36/12 x = -3 8. -21.83x - -19.9 = -23.83 -21.83x + 19.9 = -23.83 -21.83x + 19.9 - 19.9 = -23.83 - 19.9 -21.83x = -43.73 -21.83x/-21.83 = -43.73/-21.83 x = 2 9. -10x - 68 + x = 40 -9x - 68 = 40 -9x -68 + 68 = 40 + 68 -9x = 108 -9x/-9 = 108/-9 x = -12 10. -34 - 3x - 2x = 71 -34 - 5x = 71 -34 + 34 - 5x = 71 + 34 -5x = 105 -5x/-5 = 105/-5 x = -21 11. 3x - 77 - 8x = 23 -5x - 77 = 23 -5x - 77 + 77 = 23 + 77 -5x = 100 -5x/-5 = 100/-5 x = -20 12. 3x - 5(2x - 12) = 123 3x - 10x + 60 = 123 -7x + 60 = 123 -7x + 60 - 60 = 123 - 60 -7x = 63 -7x/-7 = 63/-7 x = -9 13. -3x + 6(x + 6) = 15 -3x + 6x + 36 = 15 3x + 36 = 15 3x + 36 - 36 = 15 - 36 3x = -21 3x /3 = -21/3 x = -7 14. 5x + 2(4x - 9) = -174 5x + 8x - 18 = -174 13x - 18 = -174 13x - 18 + 18 = -174 + 18 13x = -156 13x/13 = -156/13 x = -12 15. -3x + 6(5x + 3) = -171 -3x + 30x + 18 = -171 27x + 18 = -171 27x + 18 - 18 = -171 - 18 27x = -189 27x/27 = -189/27 x = -7
You might be interested in
Answer:
Step-by-step explanation:
The +k part of the function takes the original function and translates it straight up k units. It's as simple as that. If your function is the line f(x) = 3x, then the function f(x) = 3x + 4 moves that first function up 4 units.
You can make purchases even when you don't have cash hope this helps
Answer:
y = -x + 2
Step-by-step explanation:
(-3,5) and (4,-2)
Slope: (-2-5)/(4 - - 3) = -7/7 = -1
y-intercept= -2 - (-1)(4) = -2 + 4 = 2
Answer:
D = 1
Step-by-step explanation: